The Influence of Human Resource Development on the Professionalism and Integrity of Police Members - Nur Awal; Jasni Atika (Generasi Sains Indonesia, 2025)
This empirical study examines how professionalism and integrity in policing are developed, questioning the belief that they are primarily shaped through recruitment or bureaucratic promotion. Using a quantitative design with a survey of 125 officers in Takalar, South Sulawesi, it evaluates the behavioural effects of four key human resource strategies: training, ethical guidance, career systems, and recruitment mechanisms. The findings reveal that programs combining learning and moral development produce stronger behavioural outcomes than formal structural tools. Training and ethical coaching serve as core mechanisms that shape cognitive, emotional, and moral orientations in officers, proving more effective than administrative approaches. Meanwhile, career management and recruitment structures function more as symbolic systems, emphasizing procedures over practical performance improvement. This study contributes by offering empirical clarity that professionalism and integrity are not mere institutional constructs but are cultivated through continuous and ethically grounded developmental practices. Reforms that ignore these formative processes risk becoming superficial and ineffective. Sustainable integrity, therefore, must stem from consistent moral training and value-based leadership development rather than bureaucratic routines or structural displays.